Pengaruh Gaya Kepemimpinan dan Dukungan Kelembagaan Desa terhadap Kinerja BUM Desa Melalui Kapabilitas Inovasi di Provinsi Jawa Barat - Siti Nurmu’minah Fitriah; Wachyu Hari Haji (Jurnal Ragam Pengabdian, 2026)
This study explores how leadership style and village institutional support contribute to the performance of Village-Owned Enterprises (BUM Desa), with innovation capability acting as a mediating mechanism in West Java. The research is grounded in the observed decline in BUM Desa performance rankings during the 2023–2024 period, which signals persistent limitations in sustaining and improving long-term BUM Desa performance. Existing empirical studies indicate that the performance of BUM Desa is closely linked to internal organizational dynamics, particularly leadership effectiveness, institutional arrangements at the village level, and the capacity to foster innovation. To empirically investigate these relationships, this study employs a quantitative approach with a causal explanatory design. Survey data were collected from 540 employees of legally established BUM Desa in West Java, with the sample size determined using the Slovin formula. The data were obtained through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The findings reveal that leadership style and village institutional support have a positive and statistically significant effect on BUM Desa performance. In addition, innovation capability directly enhances BUM Desa performance and partially mediates the effects of leadership style and institutional support on performance outcomes. These results underscore the strategic role of innovation capability as a key pathway through which leadership and institutional support translate into improved BUM Desa performance. Consequently, efforts to strengthen BUM Desa performance in West Java should prioritize the development of effective leadership practices and consistent institutional support to reinforce innovation capability and promote sustainable BUM Desa performance